EFEKTIVITAS PERANGKAT PEMBELAJARAN METODE OUTDOOR LEARNING UNTUK MENGEMBANGKAN ASPEK FISIK MOTORIK ANAK USIA DINI - Retno Dwi Astuti (JCE (Journal of Childhood Education), 2020)
This study aims to describe the effectiveness of the development of outdoor learning method learning tools through miniature outbound activities to develop the physical aspects of motoric early childhood. The design of this research is research and development (R&D). The learning device development model used in this study is to use the 4D instructional development design proposed by Thiagarajan which consists of 4 stages of development namely Define, Design, Develop, and Disseminate. The findings of this research and development are in the form of learning tools that have previously been tested, evaluated, until they meet the desired criteria. Learning tools developed include the Semester Program (Prosem), Weekly Learning Implementation Plan (RPPM) and Daily Learning Implementation Plan (RPPH). The results of hypothesis testing using the paired sample t-test test formula obtained tcount = 4.131 and ttable = 2.045. Because tcount> ttable, Ho was not accepted and Ha was accepted. Based on SPSS results and paired sample t-test test manual formula shows that Ha is accepted, so it can be proven that there are significant differences in learning outcomes between group B children before using an outdoor learning method with group B children after using the outdoor learning method learning device.